A Rare Case of Human Coronavirus 229E Associated with Acute Respiratory Distress Syndrome in a Healthy Adult. (15th April 2018) - Vassilara, Foula; Spyridaki, Aikaterini; Pothitos, George; Deliveliotou, Athanassia; Papadopoulos, Antonios
Abstract : Human coronavirus 229E (HCoV-229E) is one of the first coronavirus strains being described. It is linked to common cold symptoms in healthy adults. Younger children and the elderly are considered vulnerable to developing lower respiratory tract infections (LRTIs). In particular, immunocompromised patients have been reported with severe and life-threatening LRTIs attributed to HCoV-229E. We report for the first time a case of LRTI and acute respiratory distress syndrome developed in a healthy adult with no comorbidities and HCoV-229E strain identified as the only causative agent. A 45-year-old female with a clear medical history presented with fever, cough, and headache. Respiratory tract infection was diagnosed, and empirical antibiotics were started. Within two days, she developed bilateral pleural effusions, diffuse consolidations, and ground glass opacities involving all lung fields. She needed immediate oxygen supply, while ABGs deteriorated and chest imaging and PaO2 /FiO2 indicated ARDS. Early administration of systemic corticosteroids led to gradual clinical improvement. Multiplex PCR from nasal secretions was positive only for HCoV-229E and negative for multiple other pathogens. It remains to be elucidated how an immunocompetent adult developed a life-threatening LRTI caused by a "benign considered" coronavirus strain, the HCoV-229E.